Fuel and acorns: Early Neolithic plant use from Cueva de Chaves (NE Spain). (1st November 2017) - Alcolea, Marta; Utrilla, Pilar; Piqué, Raquel; Laborda, Rafael; Mazo, Carlos
Abstract: Cueva de Chaves is a particularly important archaeological site for the Early Neolithic of the northeast Iberian Peninsula. This study focuses on the archaeobotanical analysis of wood charcoals and charred fruits from two Neolithic levels dated from 5678 ± 50 to 5073 ± 107 cal BC. Charcoal analysis reveals the exploitation of firewood resources in different environments. A great variety of woody taxa and plant formations dominated by pines and oaks has been documented. The location of the archaeological site in a mid-mountain environment favors a mixed exploitation of resources in the valley and the mountains. Mesophytes indicate a relative humid environment where xerophytic and thermophilous trees and shrubs have an important presence. Taxonomic richness documented in the settlement provides an idea of long-term settling and development of diversified activities. The dramatic increase of colonizing secondary formations in the earliest level of occupation can only be explained by human intervention. According to pollen information human activity in the environment is well-documented since Early Neolithic that reveal the presence of several herbaceous plants ( Plantago, Rumex, Chenopodiaceae, Asphodellus, etc). Among charred seeds we have only documented the presence of abundant and well-preserved acorns ( Quercus sp.) but the presence of crops has not been attested just by indirect archaeological evidences.